Positive Counseling And Group Dynamics For Slow Learner Independence: Konseling Positif dan Dinamika Kelompok untuk Kemandirian Siswa yang Lambat Belajar - Arpina Arpina; Bayu Pamungkas (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Inclusive education policies mandate equitable psychological and pedagogical support for all learners, particularly those with diverse cognitive profiles. Specific Background Borderline intellectual functioning places adolescents at substantial risk of chronic academic failure, necessitating proactive interventions to build self-regulation, initiative, and responsibility. Knowledge Gap Conventional school guidance predominantly relies on reactive, deficiency-based remediation rather than leveraging positive psychological resources and collaborative peer interactions to build autonomy. Aims This Classroom Action Research investigates the application of strength-based cooperative therapy to cultivate academic autonomy among marginalized adolescents within an inclusive junior high school setting. Results Following two cyclical interventions incorporating gratitude exercises, hope mapping, and collaborative support, participants' autonomous engagement metrics transitioned from a low baseline of 38.1 percent to a very high category of 89.1 percent. Observational assessments further confirmed substantial progression in self-confidence, collaborative participation, and academic self-regulation. Novelty This research distinctly integrates positive psychology principles with peer therapeutic factors, shifting the intervention paradigm from deficit correction to psychological strength optimization. Implications Educational institutions must prioritize strength-based cooperative therapies as a primary preventative framework to foster holistic academic autonomy among vulnerable student populations. Highlights Strength-based therapeutic interventions significantly elevate academic autonomy and self-regulation among marginalized adolescents. Iterative cooperative peer support strategies successfully transition at-risk individuals from passive dependency to active classroom participation. Psychological resource optimization drastically transitions autonomous engagement metrics from low baseline levels to exceptional proficiency. Keywords Positive Psychology; Inclusive Education; Academic Autonomy; Classroom Action Research; Therapeutic Peer Support